Sharing and connecting information in the context of the Covid-19 pandemic and training skills for employees to meet the needs of businesses in digital transformation - Hang Nguyen Thi; Tran Trong Quyen (Zielona Góra: Faculty of Economics and Management Press)
In the context of the strong outbreak of the Covid-19 pandemic leading to increasing social distancing, it is difficult for businesses to access the labor market. Therefore, it is necessary to create a connection channel between the employer and the labor supplier. That helps to adapt to the context of the Covid-19 pandemic, while also taking advantage of the achievements from the Industrial Revolution 4.0.
Keywords: digital economy; digital education; digital transactions; high-quality human resources; digital enterprise